A Study to Assess the Effectiveness of Chest Binder on Reduction of Pain and Kinesiophobia Among Coronary Artery Bypass Grafting Patients: A Prospective Experimental Study - Prabhudessai, Vaibhavi N; Nitte, Harish Deyannavar; Bhupali, Preeti; Sudhakar M, Sudhakar M; M V, Anju (Journal of Neonatal Surgery, 2025)
Background: Coronary Artery Bypass Grafting (CABG) is associated with pain and kinesiophobia, which can hinder rehabilitation. This study evaluates the effectiveness of chest binders in reducing these challenges. Objective:To assess pain and kinesiophobia levels in CABG patients and evaluate the impact of chest binders over two weeks. Methods: A prospective experimental study was conducted with 60 hemodynamically stable post - CABG patients aged 40–80 years. Pain and kinesiophobia levels were measured using the Visual Analogue Scale (VAS) and the Tampa Scale for Kinesiophobia – Heart (TSK-Heart) respectively, pre intervention. Chest binders were applied, and post-test assessments were conducted after 7 and 14 days. Data analysis was performed using Wilcoxon Signed Rank and Mann-Whitney tests. Results:Statistically significant reductions in mean pain scores (Day 7: 43.45; Day 14: 39.51; p < 0.05) and kinesiophobia scores (Day 7: 43.42; Day 14: 35.82; p < 0.05) were observed post-intervention (following chest binder application over two weeks). Conclusion: Chest binders are effective in alleviating pain and kinesiophobia in CABG patients, thereby facilitating early rehabilitation. Conclusion: Chest binders effectively reduce pain and kinesiophobia in CABG patients, facilitating improved rehabilitation outcomes.